Phylogenomic, Pan-genomic, Pathogenomic and Evolutionary Genomic Insights into the Agronomically Relevant Enterobacteria Pantoea ananatis and Pantoea stewartii - De Maayer, Pieter; Aliyu, Habibu; Vikram, Surendra; Blom, Jochen; Duffy, Brion; Cowan, Don A.; Smits, Theo H. M.; Venter, Stephanus N.; Coutinho, Teresa A. (Frontiers in Microbiology, 2017)
Pantoea ananatis is ubiquitously found in the environment and causes disease on a wide range of plant hosts. By contrast, its sister species, Pantoea stewartii subsp. stewartii is the host-specific causative agent of the devastating maize disease Stewart’s wilt. This pathogen has a restricted lifecycle, overwintering in an insect vector before being introduced into susceptible maize cultivars, causing disease and returning to overwinter in its vector. The other subspecies of P. stewartii, subsp. indologenes, has been isolated from different plant hosts and is predicted to proliferate in different environmental niches. Here we have, by the use of comparative genomics and a comprehensive suite of bioinformatic tools, analyzed the genomes of ten P. stewartii and nineteen P. ananatis strains. Our phylogenomic analyses have revealed that there are two distinct clades within P. ananatis while far less phylogenetic diversity was observed among the P. stewartii subspecies. Pan-genome analyses revealed a large core genome comprising of 3,571 protein coding sequences is shared among the twenty-nine compared strains. Furthermore, we showed that an extensive accessory genome made up largely by a mobilome of plasmids, integrated prophages, integrative and conjugative elements and insertion elements has resulted in extensive diversification of P. stewartii and P. ananatis. While these organisms share many pathogenicity determinants, our comparative genomic analyses show that they differ in terms of the secretion systems they encode. The genomic differences identified in this study have allowed us to postulate on the divergent evolutionary histories of the analyzed P. ananatis and P. stewartii strains and on the molecular basis underlying their ecological success and host range.